2022
DOI: 10.1039/d2an00031h
|View full text |Cite
|
Sign up to set email alerts
|

A study of protein–drug interaction based on solvent-induced protein aggregation by fluorescence correlation spectroscopy

Abstract: Identifying the molecular targets for the beneficial effects of small-molecule drugs is a crucial and currently unsolved challenge which leads to high costs and long development cycles. Therefore, it is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…† One kind of FCS curve (red curve) was similar to the previously reported FCS curves of protein monomers, and we attributed it to the contribution of the EGFP-LC3B monomer only. 30 Another kind of FCS curve (blue curve) shifted significantly to the right compared with the former and exhibited different characteristic from that of the fluorescent monomer and EGFP-LC3B monomer, and we attributed it to the contribution of the EGFP-LC3B punctae and EGFP-LC3B monomer. 30 The absolute values of the fitting residuals were almost less than 0.4 indicating that the two typical kinds of FCS curves can be well fitted.…”
Section: The Monitoring Of Autophagosomes In Living Cellsmentioning
confidence: 73%
See 2 more Smart Citations
“…† One kind of FCS curve (red curve) was similar to the previously reported FCS curves of protein monomers, and we attributed it to the contribution of the EGFP-LC3B monomer only. 30 Another kind of FCS curve (blue curve) shifted significantly to the right compared with the former and exhibited different characteristic from that of the fluorescent monomer and EGFP-LC3B monomer, and we attributed it to the contribution of the EGFP-LC3B punctae and EGFP-LC3B monomer. 30 The absolute values of the fitting residuals were almost less than 0.4 indicating that the two typical kinds of FCS curves can be well fitted.…”
Section: The Monitoring Of Autophagosomes In Living Cellsmentioning
confidence: 73%
“…30 Another kind of FCS curve (blue curve) shifted significantly to the right compared with the former and exhibited different characteristic from that of the fluorescent monomer and EGFP-LC3B monomer, and we attributed it to the contribution of the EGFP-LC3B punctae and EGFP-LC3B monomer. 30 The absolute values of the fitting residuals were almost less than 0.4 indicating that the two typical kinds of FCS curves can be well fitted. As a comparison, we also constructed the HeLa cells, H1299 cells and HEK293T cells stably expressing EGFP-LC3BΔG and EGFP.…”
Section: The Monitoring Of Autophagosomes In Living Cellsmentioning
confidence: 73%
See 1 more Smart Citation
“…Due to the lack of drugs for diseases caused by protein aggregation related to protein LLPS, identifying biomolecules inhibiting abnormal LLPS and evaluating their inhibitory effects have become important research directions for the development of therapeutic approaches against related protein diseases. Some biomolecules can stabilize protein structures and thus inhibit protein phase separation, such as ATP, which forms ATP clusters on the surface of proteins by binding with highly flexible or hydrophobic regions, thus improving the stability of thermal perturbations. In our previous studies, we have found FCS to be a reliable research tool for obtaining data on the inhibitory effects of drugs on target proteins. , Therefore, in this section, we tried to evaluate the inhibitory effect of some biomolecules on protein phase separation by FCS.…”
Section: Resultsmentioning
confidence: 99%
“…37−39 In our previous studies, we have found FCS to be a reliable research tool for obtaining data on the inhibitory effects of drugs on target proteins. 40,41 Therefore, in this section, we tried to evaluate the inhibitory effect of some biomolecules on protein phase separation by FCS.…”
Section: Validation Of the Phase Separation Behavior Of Fus-egfp By Fcsmentioning
confidence: 99%